Hard-working Heroes or Curious Students? - Au pair Positioning, Organizing, and Negotiation - Hansen, Agnete Meldgaard; Pedersen, Maria Hjortsø (Nordic Journal of Working Life Studies, 2019)
The precarious position and poor working conditions of au pairs in the Nordic and other western labor markets are well documented. Furthermore, research on au pairs and migrant domestic workers emphasizes many obstacles to their organizing (e.g., in trade unions) and negotiation to improve their working conditions. Using an ethnographic study of Filipino au pairs in Denmark as an illustrative case, we supplement this previous research by presenting an analytical approach inspired by governmentality studies. This approach highlights the complex transnational interplay of migration policies and practices affecting Filipino au pairs’ positioning in the Danish labor market and contributes to exploring how this positioning relates to their prospects for negotiating and organizing. We suggest that with a close examination of the often contradictory and multifaceted positioning of migrant workers in transnational policy fields, not only obstacles but also possibilities for negotiation and organizing to improve working conditions will become visible